Design and preliminary evaluation of a track-based robotic colonoscope with a shape-adaptable tip for propulsion - Jiayang Du; Lin Cao; Sanja Dogramadzi (Frontiers in Robotics and AI)
This paper introduces a shape-adaptable robotic endoscope design, which combines an expansion mechanism and external drive system that provide tip insertion force and adjust the tip shape and size to different colon diameters. Expansion rate of 53% has been achieved in the expandable tip size, which corresponds to changes in the colon diameter. We tested the prototype locomotion in a pipe with different friction surface layers, including artificial bowel tissues, to assess propulsion force and normal force on the colon that can be achieved with the current design. The prototype can generate a propulsion force of 2.83 N, and the maximum linear speed of 29.29 mm/s on the artificial tissue surface. It can produce effective propulsion when it passes through pipes of different diameters. The results demonstrate the prototype’s ability for shape adaptation that maintains the required traction force on the bowel wall.